Regulatory Effects of Diverse DSF Family Quorum-Sensing Signals in Plant-Associated Bacteria - Kaihuai Li; Chaoyun Ma; Xue Zhou; Chunlan Xiong; Bo Wang; Yong Wang; Fengquan Liu (Molecular Plant-Microbe Interactions, 2024)
Numerous bacterial species employ diffusible signal factor (DSF)-based quorum sensing (QS) as a widely conserved cell–cell signaling communication system to collectively regulate various behaviors crucial for responding to environmental changes. cis-11-Methyl-dodecenoic acid, known as DSF, was first identified as a signaling molecule in Xanthomonas campestris pv. campestris. Subsequently, many structurally related molecules have been identified in different bacterial species. This review aims to provide an overview of current understanding regarding the biosynthesis and regulatory role of DSF signals in both pathogenic bacteria and a biocontrol bacterium. Recent studies have revealed that the DSF-based QS system regulates antimicrobial factor production in a cyclic dimeric GMP-independent manner in the biocontrol bacterium Lysobacter enzymogenes. Additionally, the DSF family signals have been found to be involved in suppressing plant innate immunity. The discovery of these diverse signaling mechanisms holds significant promise for developing novel strategies to combat stubborn plant pathogens. [Graphic: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.